Online Fatigue-Monitoring Models with Consideration of Temperature Dependent Properties and Varying Heat Transfer Coefficients - HengLiang Zhang; Shi Liu; Danmei Xie; Yangheng Xiong; Yanzhi Yu; Yan Zhou; Rui Guo (Science and Technology of Nuclear Installations)
Thermal stress failure caused by alternating operational loads is the one of important damage mechanisms in the nuclear power plants. To evaluate the thermal stress responses, the Green’s function approach has been generally used. In this paper, a method to consider varying heat transfer coefficients when using the Green’s function method is proposed by using artificial parameter method and superposition principle. Time dependent heat transfer coefficient has been treated by using a modified fluid temperature and a constant heat transfer coefficient. Three-dimensional temperature and stress analyses reflecting entire geometry and heat transfer properties are required to obtain accurate results. An efficient and accurate method is confirmed by comparing its result with corresponding 3D finite element analysis results for a reactor pressure vessel (RPV). From the results, it is found that the temperature dependent material properties and varying heat transfer coefficients can significantly affect the peak stresses and the proposed method can reduce computational efforts with satisfactory accuracy.